Subclinical hypothyroidism and cardiovascular risk factors - Delitala, Alessandro P; Scuteri, Angelo; Maioli, Margherita; Mangatia, Paolo; Vilardi, Luca; Erre, Gian Luca (Minerva medica, 2019)
Thyroid hormones have multiple effects on lipid metabolism as well as on the cardiovascular system function. These negative cardiovascular effects have long been recognized in overt hypothyroidism but can be reversed by treatment with levothyroxine. We performed on PubMed a literature search for the articles published until March 2019 by using the search terms "subclinical hypothyroidism," "cardiovascular disease," "cholesterol," "LDL," "HDL," "triglycerides," "coronary heart disease," "heart failure," "atherosclerosis," "all-cause mortality," "levothyroxine." Subclinical hypothyroidism, defined as an elevated thyrotropin (TSH) with a normal free thyroxine (FT4), is frequent in the general population and increase with age. Subclinical hypothyroidism has been linked to cardiovascular risk factors, dyslipidemia and increased atherosclerosis. Although some studies have demonstrated that lipids are elevated in subclinical hypothyroidism, other studies did not confirm these data. Clinical trials have also demonstrated there is no clear evidence that levothyroxine therapy in subjects with milder form (TSH<10 mU/L) of subclinical hypothyroidism could improve lipid status and the other cardiovascular risk factors. Nevertheless, TSH level seems the best predictor of cardiovascular disease, in particular when its levels are above 10 mU/L. Prospective studies are necessary to clarify the cardiovascular risk in patients with mild subclinical hypothyroidism and to assess the importance of treating elderly people in order to improve or counteract the correlated risks. However, until clinical recommendations will be updated, the decision to treat or not treat patients with subclinical hypothyroidism will still base on clinical judgment, clinical practice guidelines, and expert opinion.